Technology-Enhanced Collaborative Learning Model Between Industry and Universities to Improve Graduate Employability - Zumrotul Avifa K (Jurusan Teknik Informatika dan Komputer, 2025)
This study examines the influence of technology-enhanced collaborative learning and industry–university collaboration on graduate employability, with learning engagement analyzed as a mediating psychological mechanism. Conducted at Universitas Tomakaka, the research employs a quantitative explanatory design using structured questionnaires and EViews-based modeling to test direct and indirect effects. The findings demonstrate that technology-enhanced collaborative learning significantly contributes to employability by strengthening students’ digital communication, problem-solving abilities, and collaborative competencies. Industry–university collaboration also shows a strong direct effect on employability, reflecting the importance of workplace exposure, authentic project assignments, and industry-level feedback in preparing students for professional roles. Mediation analysis further confirms that learning engagement partially mediates both relationships, revealing that active, emotional, and cognitive involvement enhances the translation of learning experiences into employability outcomes. Engagement emerges as a critical mechanism through which students internalize collaborative learning environments and industry expectations, transforming them into concrete professional skills. These findings highlight that employability development is not merely the result of structural or technological interventions but depends heavily on the psychological processes that shape how students participate in and interpret their learning experiences. This study concludes that integrating digital collaborative learning with structured industry partnerships is essential for producing competent, work-ready graduates.